Increasing of down passing skills for mini volleyball game by using reciprocal teaching model - Syamsuar Abbas; Reflianto Reflianto (Fakultas Ilmu Pendidikan UNP)
The aim of this study was to increase students’ down passing skill for miny volleyball game at class of elementary school by using reciprocal teaching model. Reciprocal teaching model can increase the activity of students in participating to the teacing-learning process. The implementation of this model gave a positive impact on the students’ agility and physical fitness particularly for increasing students’ down passing skill in the game of mini volleyball. This study used a research and development method. Subjects of this study were fifth grade students from elementary. The result of this result reported that by using reciprocal teaching model can improve students’ down passing skill in the playing of Mini Volleyball game and enhyances students’ physical fitness and health as well as master with basic technique of the mini volleyball game. Sport education teacher could use this model to Elementary students level for improving their down passing skill in the game of mini volleyball.